Transformational Leadership Style in Human Resource Management: A Case Study in a Multinational Company - Asraf Asraf; Laode Muhammad Khalilintar Lutfi; Muhammad Nuzul Qadri (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Transformational leadership has been recognized as a key factor in enhancing organizational effectiveness and driving innovation across industries. In the context of multinational companies, this leadership style becomes even more important given the complexities arising from cultural differences, regulations, and workforce expectations. This study aims to identify these challenges and formulate effective strategies for transformational leaders in managing a diverse workforce in multinational companies. This study uses a qualitative descriptive method with a case study approach, where data were collected through semi-structured interviews with five informants from various organizational levels in a multinational company. The results show that transformational leadership contributes to increased employee engagement and productivity, although its implementation faces significant challenges, such as cultural differences and regulations across countries. Therefore, more flexible and technology-based strategies need to be developed to optimize the effectiveness of transformational leadership in a global context. These findings contribute to the development of transformational leadership theory and provide practical guidance for management strategies in multinational companies to manage human resources more adaptively and innovatively.